Interrelations of Municipal and State Budgets in the Republicof Armenia and the Impact of Budget Proportions on Regional Economic Development - Galstyan, Hamazasp; Badadyan, Gagik; Tatosyan, Kristine («Տնտեսագետ» հրատ․)
The implementation of the state budget designed by the central government bodies in each country aims at improving the socioeconomic condition of the country and solving the existing problems related to that condition. The differentiation of the levels of socioeconomic development of territorial units is quite important. Disparities in territorial development are characteristic of all countries in the world, but it is another matter that the degree of these disparities can be significantly different for different countries. Regardless of the degree of disparities, the central government bodies of countries try to distribute budget funds in such a way that it is possible to overcome the disparities of territorial development, or at least reduce them to a minimum level. The relations between the state and local budgets are of essential importance in that process, when a part of municipal budget revenues is generated due to these relations. In this regard, the Republic of Armenia is not an exception, and there is an objective need to study the relationship between the budget revenues of the municipalities of the Republic of Armenia (in the form of the regional total) and the development level of the regions.
Keywords: Regional developments